Lexical Cohesion and Translation Equivalence - Lotfipour-Saedi, Kazem (Meta, 1997)
AbstractAccording to modem trends in linguistics, a text rather than a sentence is the unit of communication, and communication and negotiation of meanings in human verbal transactions is achieved within the framework of a text. Among the features which contribute to the texture of a text and distinguish it from a non-text, cohesion has been argued to be an important one. Halliday and Hasan (1976) have described different types of cohesion (grammatical, lexical and conjunction). In this paper we would like to define the notion of Translation Equivalence (TE) in terms of lexical cohesion. The type of lexical strategies employed by the SL discourse producer, the nature of the cohesive network (predictive, prospective as well as retrospective) created by such strategies and the type of semantic structures which exist among the lexical nodes in this network will first be characterized. Then the TL equivalent text will be examined in terms of similar lexical strategies.